PERBEDAAN PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER (NHT) DAN JIGSAW TERHADAP PRESTASI BELAJAR SEJARAH SISWA DITINJAU DARI MOTIVASI BELAJAR SEJARAH SISWA - Rambe, Yasir Maulana; Akhyar, Muhammad; Musadad, Akhmad Arif (HISTORIKA, 2018)
The objectives of research were (1) to find out the different effects of Numbered Heads Together (NHT) and Jigsaw types of cooperative learning use on the historical learning achievement of students, (2) to find out whether or not historical learning motivation affects the historical learning achievement of students, and (3) to find out whether or not there is a positive effect of interaction between Numbered Heads Together (NHT) and Jigsaw types of cooperative learning model, and learning motivation on the learning achievement of students. If there is so, which type has better effect?This study employed quantitative method with a 2x3 factorial design. The population of research was the 10th graders of Senior High Schools existing in Sukoharjo in the even semester in the school year of 2015/2016. The sampling technique used in this research was Cluster Sampling (Area Sampling). The sample of research consisted of SMA Negeri 1 Kartasura with 36 students and SMA Negeri Mojolaban with 33 students. The techniques of collecting data used were test and questionnaire. Data analysis in this research employed a two-way anava with SPSS 20 program help.Â  The results of hypothesis testing in this research were shown as follows. (1) There was a difference of effect on the learning achievement between the students treated with Numbered Heads Together and those treated with Jigsaw types of learning model. The result of data analysis showed that the students treated with Numbered Heads Together had better learning achievement than those treated with Jigsaw learning model. (2) There was a difference of effect between the students with high, medium, and low learning motivations. The students with high learning motivation had better learning achievement than those with medium one, and those with medium learning motivation had better learning achievement than those with low one. (3) There was no interaction effect between learning model and learning motivation on the historical learning achievement. The students with high learning motivation treated with Numbered Heads Together (NHT) learning model had better learning achievement than those high learning motivation treated with Jigsaw learning model. The students with medium learning motivation treated with Numbered Heads Together (NHT) learning model had better learning achievement than those medium learning motivation treated with Jigsaw learning model, and the students with low learning motivation treated with Numbered Heads Together (NHT) learning model had better learning achievement than those low learning motivation treated with Jigsaw learning model.